Civil Liability in Medical Malpractice Cases in Private Hospitals - Henny Saida Flora (PT. Anagata Sembagi Education, 2025)
This study examines civil liability in medical malpractice cases in private hospitals in Indonesia, which still face legal uncertainty due to the difference in the basis of claims between unlawful acts and breach of contract, as well as the limited application of the vicarious liability principle. This study uses a normative juridical method with a statutory, conceptual, and case-based approach, utilizing secondary data from legal literature, regulations, and court decisions related to medical malpractice. The results show that the application of vicarious liability in private hospitals is often hampered by the partnership-based working relationship between doctors, allowing hospitals to avoid direct liability. Furthermore, disharmony between the Civil Code, the Health Law, the Hospital Law, and the Consumer Protection Law creates evidentiary obstacles and jurisprudential inconsistencies. The discussion underscores the need for regulatory harmonization, national guidelines for proving medical malpractice, and affirmation of the direct liability of private hospitals to strengthen patient legal protection. In conclusion, increasing legal certainty and patient protection requires regulatory reform and consistent application of the civil liability principle, which is also expected to encourage improved quality of healthcare services in private hospitals.